Significance of Diagnosis in Efficient Disease Control in Aquaculture and Fisheries - Tyagi, Vidhi; Baliyan, Rakhi; Kumari, Archana; Yasmin, Reshman; Mishra, Induja; Nath, Pashupati (Journal of Neonatal Surgery, 2025)
Aquaculture is an important and rapidly growing component of agriculture worldwide and contributing 44 % of total fish production globally. Diagnosis is an indicator or marker given for a disease condition to identify by its signs, symptoms, and from the various diagnostic procedures. The correct identification will further aid in accurate disease diagnostics, proper treatment, and medication. As also performed in human diseases, the diagnosis information and case history, clinical signs should be carefully used while probing samples for the diagnosis can also be useful in aquaculture systems. The most significant approach to decrease or prevent the losses due to diseases is early disease diagnosis, monitoring at regular intervals, and proper action at the first sign at any unfavorable condition. The diagnostic tools and techniques are gaining greater importance in aquaculture diseases due to their specificity, sensitivity, speed and correctness. Effective disease control is the outcome of early diagnosis; afterwards the control and management will be implemented. This strategic manner will be more effective to prevent spread of individual disease to become a disease outbreak.